The genus Afrasura Durante, 2009 in Gabon, with description of five new species and a new species group (Erebidae: Arctiinae: Lithosiini) - Durante, Antonio (Zootaxa, 2012)
The author presents the first work on two surveys in the National Park of Ivindo in Gabon. He examines the genusAfrasura Durante, 2009, describes the female of A. emma Durante, 2009, and five new species: A. trunca sp. n., A. camillasp. n., A. duplex sp. n., A. aetheria sp. n., A. fracta sp. n., of which the last four belong to the newly proposed A. submarmorata species group.